2021
DOI: 10.2186/jpr.jpor_2019_553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of zirconia surface treatments of a bilayer restorative assembly on the fatigue performance

Abstract: This study evaluated the influence of different surface treatments of zirconia used to enhance bonding with veneering porcelain, and thermocycling on the resistance to porcelain cracking and delamination during fatigue test. Methods: Bilayer ceramic discs were made from zirconia blocks (IPS e.max Zircad MO, Ivoclar Vivadent-0.7 mm thickness) and randomized into 8 groups (n= 15) according to two factors: 'zirconia surface treatment' (Control; Grinding-diamond bur; Air-abrasion-aluminum oxide particles; and Line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Harding et al supported previous studies that revealed that sandblasting with alumina particles did may affect roughness [20,23] but, on the other hand, may decrease flexural strength [23]. Valandro et al stated that neither the surface treatment of zirconia nor the thermocycling influences the porcelain crack resistance or the resistance to delamination of bilayer porcelain-veneered zirconia specimens [39].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Harding et al supported previous studies that revealed that sandblasting with alumina particles did may affect roughness [20,23] but, on the other hand, may decrease flexural strength [23]. Valandro et al stated that neither the surface treatment of zirconia nor the thermocycling influences the porcelain crack resistance or the resistance to delamination of bilayer porcelain-veneered zirconia specimens [39].…”
Section: Discussionmentioning
confidence: 60%
“…The tribochemical silica coating achieved by using the Cojet system spread a silica layer on the ceramic surface, due to the high-pressure impact of alumina particles modified by silica on the conditioned substrate [21,38]. Such a technique is supposed to provide ultrafine mechanical retention by embedding treated surfaces with silica particles and improve chemical bonding [21,39,40]. Different punctual micro-analysis conducted on the cross section of the specimens at the interface zirconiaveneering ceramic pointed out that silica coating generated a reaction area.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we prepared the specimens in the present study by either diamondgrinding or sandblasting to isolate the influence of each treatment. Machado et al also investigated the crack and delamination resistance of bilayered zirconia and compared three surface-treatment groups: sandblasted, ground, and liner-applied 33) . The liner-applied zirconia exhibited the lowest fatigue performance in terms of crack resistance; however, no statistical differences in delamination resistance were observed among the groups.…”
Section: Discussionmentioning
confidence: 99%